A CONTEXTUAL ACCOUNT OF MOTHERHOOD - Frizelle, Kerry; Kell, Gabrielle (PINS-Psychology in Society, 2025)
The data for this paper was originally collected and analysed by the second author for her master’s thesis. The first author (the second author’s supervisor) has re-visited and re-worked the data and analysis for the purposes of this paper. The data was collected during two focus groups with six, white middle-class South African mothers. The study adopted a feminist method of analysis, the voice-relational method, with the aim of opening up for exploration the way in which mothers’ everyday experiences of mothering are impacted on by the specific social context in which they are embedded. The voice-relational method of analysis, based on the principles of relational ontology, proved a useful tool to explore the way in which individual mothers’ experiences are informed by their location within particular relational, structural and cultural contexts. The analysis reveals the way in which race, class, sexual orientation and gender intersect with dominant ideologies of motherhood to inform the experiences of suburban, middle-class women negotiating, within a complex set of relationships, what it is to be a mother.